1988
DOI: 10.1111/j.1365-2885.1988.tb00196.x
|View full text |Cite
|
Sign up to set email alerts
|

Gizzard ulceration in chicks fed cysteamine alone or in combination with a histamine H2‐receptor antagonist

Abstract: A study was carried out to evaluate the effect of cysteamine-HCl administration on gizzard ulceration and growth performance in broiler chicks. The effectiveness of the histamine H2-receptor antagonist, SKF 93479, in preventing gizzard ulcerations when given in combination with cysteamine-HCl was also examined. In the initial experiment cysteamine-HCl at the level of 2400 mg/kg of the diet caused severe gizzard ulceration and mortality and decreased feed intake and growth in chicks. The effect was not seen whe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1993
1993
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…Although the main focus has been placed on the appearance of clinical signs of the erosion, the toxic effects of gizzerosine could have an earlier manifestation in affecting growth performance without the clinical symptoms. In fact, growth rates have been affected by additions of gizzerosine to the diet (> lppm) (Sugahara et ah, 1988), and other compounds with gizzard-ulceration activity have also been reported to decrease growth performance (Zavy et al, 1988). No studies have been reported of the effects of gizzerosinelike activity on growth performance of commercially raised fish, another species in which fish meal is a main source of dietary protein.…”
Section: Discussionmentioning
confidence: 99%
“…Although the main focus has been placed on the appearance of clinical signs of the erosion, the toxic effects of gizzerosine could have an earlier manifestation in affecting growth performance without the clinical symptoms. In fact, growth rates have been affected by additions of gizzerosine to the diet (> lppm) (Sugahara et ah, 1988), and other compounds with gizzard-ulceration activity have also been reported to decrease growth performance (Zavy et al, 1988). No studies have been reported of the effects of gizzerosinelike activity on growth performance of commercially raised fish, another species in which fish meal is a main source of dietary protein.…”
Section: Discussionmentioning
confidence: 99%
“…In the hypothalamus, CSH depletes SS to promote growth, while in the stomach it acts on gastric mucosa to promote gastric acid secretion ( Shi et al, 2006 ). High-dose CSH leads to gastric acid hypersecretion, causing gastric and duodenal ulcers ( Zavy et al, 1988 ). In broiler chickens, the growth-promoting effect of CSH has been reported ( Hu et al, 2008 ), but instance of ulcers caused by over-dose CSH was also noted ( Drago and Montoneri, 1997 ).…”
Section: Introductionmentioning
confidence: 99%